Formulation of a composite of date palm wood‐cement - Farid Touloum; Akli Younsi; Abdelhak Kaci; Adel Benchabane (Journal of Applied Engineering Science and Technology, 2017)
This work reports the results of an experimental study on the incorporation of woodwaste date palm reduced in particles for the manufacture of wood – cement composites. Thesematerials are chipper than the conventional insulator material and environmental friendly. Fivetypes of wood – cement composites with various concentrations of the wood particles, ie. 2, 4, 6, 8and 10% of total volume, were made according to defined protocol and mix design. Their thermaland mechanical properties were measured and compared to other conventional materials. Theobtained results show that the thermal conductivity is positively correlated to the content ofparticles in the mixture. The compressive strength of composites decreases where the content ofparticles increase. However, taking account of the ASTM C 109 / C109‐95 standard, the wood –cement composite contained 10% of wood particles, considered as lightweight concrete, could beused as non‐structural material in construction.